Comparison of Two Music Training Approaches on Music and Speech Perception in Cochlear Implant Users. (March 2018) - Fuller, Christina D.; Galvin, John J.; Maat, Bert; Başkent, Deniz; Free, Rolien H.
In normal-hearing (NH) adults, long-term music training may benefit music and speech perception, even when listening to spectro-temporally degraded signals as experienced by cochlear implant (CI) users. In this study, we compared two different music training approaches in CI users and their effects on speech and music perception, as it remains unclear which approach to music training might be best. The approaches differed in terms of music exercises and social interaction. For the pitch/timbre group, melodic contour identification (MCI) training was performed using computer software. For the music therapy group, training involved face-to-face group exercises (rhythm perception, musical speech perception, music perception, singing, vocal emotion identification, and music improvisation). For the control group, training involved group nonmusic activities (e.g., writing, cooking, and woodworking). Training consisted of weekly 2-hr sessions over a 6-week period. Speech intelligibility in quiet and noise, vocal emotion identification, MCI, and quality of life (QoL) were measured before and after training. The different training approaches appeared to offer different benefits for music and speech perception. Training effects were observed within-domain (better MCI performance for the pitch/timbre group), with little cross-domain transfer of music training (emotion identification significantly improved for the music therapy group). While training had no significant effect on QoL, the music therapy group reported better perceptual skills across training sessions. These results suggest that more extensive and intensive training approaches that combine pitch training with the social aspects of music therapy may further benefit CI users.